A short communication on glocal universities. (2016) - Grau, Francesc Xavier
This paper deals with the dual responsibilities of universities at local and global scale, exploring the potential conflict, or intrinsic difficulties, in addressing both local demands of society based on the race for global competitiveness and local and global demands to contribute to a more equitable and sustainable society (at local and global scales). Like many other organisations today, universities are under intense pressure, coming especially from 'local' demands. The paper analyses and proposes the elements that allow for the global and local engagement of universities. The vision of a university as a 'social force for good' makes engagement compatible with the immediate needs of local societies and the global challenges of the world. This is the real challenge of many universities all over the world that may be able to take on the responsibility of being a glocal university.